Stability of commercial phytase products stored under different environmental conditions - De Jong, J. A.; DeRouchey, Joel M.; Tokach, Michael D.; Goodband, Robert D.; Woodworth, Jason C.; Jones, Cassandra K.; Stark, Charles R.; Bradley, C. L.; Loughmiller, J. A.; Bergstrom, J. R. (My University, 2016)
A 300-d study evaluated the stability of 4 phytase products stored under varied environmental conditions. The 4 products were: 1) Quantum Blue 5G (AB Vista, Marlborough, United Kingdom); 2) Ronozyme HiPhos GT 2700 (DSM Nutritional Products, Parsippany, NJ); 3) Axtra Phy TPT (Dupont, Wilmington, DE); and 4) Microtech 5000 Plus (Guangdong VTR Bio-Tech Co., Ltd., Guangdong, China). Products were stored as pure forms at ?20, 4, 22, or 35°C (75% humidity), or in a vitamin or vitamin trace mineral (VTM) premix at 22 and 35°C (75% humidity). Samples were stored in paper bags and sampled on d 30, 60, 90, 120, 210, and 300. Stability was determined as amount of residual phytase activity (% of initial). For pure forms, all interactive and main effects of product, time, and temperature were significant (P < 0.05). From d 30 to 300, products had similar reductions in phytase activity at the 3 highest temperatures; however, Quantum Blue 5G, Ronozyme HiPhos GT 2700, and Axtra Phy TPT had reduced (P < 0.05) phytase activity compared to Microtech 5000 Plus at ?20°C. As storage time increased, residual phytase activity was reduced (P < 0.05) regardless of product and storage temperature. Also, when product was stored at 4 and 22°C, phytase activity was improved compared to ?20 and 35°C. For vitamin and VTM premixes, a time×temperature × product interaction (P < 0.05) was observed as a result of, Axtra Phy TPT and Microtech 5000 Plus having reduced residual phytase activity (P < 0.05) compared to the other 2 products when stored at 22°C, while activity of Axtra Phy TPT was reduced (P < 0.05) even further than the other 3 products when stored at 35°C regardless of form. From d 30 to 300, Axtra Phy TPT and Microtech 5000 Plus had the lowest (P < 0.05) residual phytase activity compared to the other 2 products. The VTM had decreased (P < 0.05) residual phytase activity compared to the pure product and vitamin premixes. In conclusion, phytase stored for longer than 90–120 d at 35°C or ?20°C in pure form, or when stored as a VTM premix had reduced residual phytase activity.
Citation: De Jong, J. A., DeRouchey, J. M., Tokach, M. D., Goodband, R. D., Woodworth, J. C., Jones, C. K., . . . Bergstrom, J. R. (2016). Stability of commercial phytase products stored under different environmental conditions. Journal of Animal Science, 94, 114-114. doi:10.2527/msasas2016-241
Keywords: Phytase; Storage; Stability; Agriculture